POLA SISTEM PANGAN MASYARAKAT ADAT KAMPUNG NAGA KABUPATEN TASIKMALAYA - Setiawan, Perdi; Nuryaman, Hendar; Setiawan, Iwan; Mutiarasari, Nurul Risti; Amalia, Lidya Nur; Syakirotin, Muthiah (Jurnal Agristan, 2025)
Food is a basic need whose fulfillment is mandatory and urgent and its sustainability needs to be ensured. The recent approach to food provision has highlighted the food system implemented by indigenous peoples in various regions which is still carried out traditionally and pays great attention to the balance of nature, including the indigenous people of Kampung Naga. This study aims to describe and construct the pattern of the food system that has been implemented by the indigenous people of Kampung Naga. This study was designed qualitatively using a systems thinking approach. which is depicted in a causal loop diagram (CLD) located in Kampung Naga, Neglasari Village, Salawu District, Tasikmalaya Regency. The data used in this study are primary data obtained through in-depth interviews and Focus Group Discussions (FGD) with several informants involved, while secondary data were obtained from various related literature. The results of the study indicate that the food system of the indigenous people of Kampung Naga includes various components that are interrelated with each other, such as social systems and ecological systems that intersect with production, management and processing systems, local mitigation systems and the food consumption system of the indigenous people of Kampung Naga which is still carried out traditionally and considers aspects of sustainability. The results of this study are expected to provide an overview in formulating the concept of sustainable food system management.